Active surveillance of adverse events following ChAdOx1 nCoV-19 immunization in geriatric population: a prospective multi-centric study from Jaipur, Rajasthan, India - Anil Bhandari; Surya Pratap Singh Tiwari; Monika Rathore; Lokendra Sharma; Smita Jain (Geriatric Care, 2022)
India launched its coronavirus disease 2019 (COVID-19) vaccination drive starting with healthcare workers. The aim of the study was to evaluate adverse events following immunization (AEFI) amongst the Geriatric population associated with two doses of ChAdOx1 nCoV-19 vaccine. We also evaluated association of AEFI according to gender and elderly age groups. An observational study, conducted among 437 individuals vaccinated at multiple community healthcare centers in Jaipur, of AEFIs associated with both doses of ChAdOx1 nCoV-19 vaccine, via telephonic interviews on the day of vaccination-Day 0, Day 7 and Day 15 from vaccination. 463 vaccinated individuals who responded for first dose AEFIs, and 437 (94.3% 437/463) responded to the telephone interview regarding the second dose. Of these, 5.5% (24/437) reported AEFIs for the second dose. Among 60 respondents who reported AEFI (both doses) fever (26) and fatigue (22) were the most reported systemic AEFI. Local AEFIs were injection site soreness (23). The AEFIs (both systemic and local) in respondents mostly lasted for 1-2 days. AEFI reported by respondents in the age group 60- 70 years was higher than those above 70 years. Female respondents were associated with higher AEFI than the males. The AEFIs of both the doses were observed in the first 2 days predominantly. Symptoms were minor, short lived and selflimiting. No serious adverse events attributable to vaccines were reported in our study. Adverse event following immunization is independent of gender and age distribution for both the doses.